The New El Dorado invaders and exiles. - Strauss, Theodore; Soh, John.; Cousteau Society ([s.l.] : The Cousteau Society Inc. and TBS Productions, 1984)
Shows the native Indians of the Amazon rain forest ; like victims displaced by time, strive to cope with the radical changes imposed by invaders from a modern world. Jean-Michel Cousteau travels from remote Indian Villages where ancient rituals are now performed only for tourist, to the vast of gold mines of Serra Pelada in which thousands of Brazilians toil in backbreaking labor persuing dreams of fabulous wealth.
Keywords: Social problems; Legends -- Amazon River Region; Amazon River Region -- Social conditions